Communication styles and organizational da’wah practices of the Jama’ah Tabligh in mitigating hate speech - Furqan; Abdullah; Sahrul (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2025)
This study examines the communication style of the Jama’ah Tabligh organization in mitigating hate speech within Aceh Besar, Indonesia. The research focuses on their strategies for delivering religious messages, the challenges encountered in implementing their communication approaches, and the broader implications of these practices in reducing hate-motivated expressions in the community. Employing a qualitative method, data were collected through in-depth interviews, participant observation, and document analysis conducted from January to April 2025, involving Jama’ah Tabligh members, community leaders, and local residents who regularly interact with their activities. The findings reveal that Jama’ah Tabligh adopts a da’wah bil hikmah communication style characterized by persuasive, non-confrontational, and example-driven approaches. Messages are conveyed through interpersonal communication rooted in cultural sensitivity, the use of local language, and adherence to Acehnese customs. Core activities such as khuruj (missionary travel), jaulah (house visits), and ta’lim (study gatherings) function not only as religious practices but also as mechanisms for shaping positive community perceptions and raising awareness about the dangers of hate speech. Key challenges include persistent stigma toward Jama’ah Tabligh, limited technological engagement, the prevalence of online hate narratives, and differing religious traditions among local dayah communities. The study recommends strengthened collaboration among religious organizations, local authorities, and customary leaders to formulate more effective communication strategies for countering hate speech in culturally grounded ways. ***** Penelitian ini mengkaji gaya komunikasi organisasi Jama’ah Tabligh dalam merespons dan mereduksi perilaku hate speech di Aceh Besar, Indonesia. Fokus kajian diarahkan pada strategi penyampaian pesan dakwah, dinamika penerapan gaya komunikasi dalam interaksi sosial, serta efektivitas pendekatan yang digunakan dalam menurunkan potensi ujaran kebencian di tingkat masyarakat. Menggunakan metode kualitatif dengan teknik pengumpulan data berupa wawancara mendalam, observasi partisipatif, dan studi dokumentasi, penelitian dilakukan sepanjang Januari–April 2025 terhadap anggota Jama’ah Tabligh, tokoh masyarakat, dan warga yang berinteraksi langsung dengan aktivitas dakwah mereka. Hasil penelitian menunjukkan bahwa Jama’ah Tabligh menerapkan gaya komunikasi dakwah bil hikmah yang bersifat persuasif, non-konfrontatif, dan berorientasi pada keteladanan. Pesan disampaikan melalui komunikasi interpersonal yang mengutamakan pendekatan kultural, penggunaan bahasa lokal, serta penghormatan terhadap nilai dan adat Aceh. Aktivitas dakwah seperti khuruj, jaulah, dan ta’lim berperan sebagai medium pembentukan persepsi positif sekaligus sarana penyadaran sosial terhadap bahaya hate speech. Hambatan yang ditemukan meliputi stereotip negatif terhadap Jama’ah Tabligh, keterbatasan teknologi informasi, intensitas ujaran kebencian di media sosial, serta perbedaan tradisi keagamaan dengan sebagian masyarakat dayah. Penelitian merekomendasikan kolaborasi antara organisasi keagamaan, pemerintah daerah, dan tokoh adat dalam membangun strategi komunikasi yang lebih efektif untuk meredam hate speech secara berkelanjutan.